Agglomeration externalities and urbanization in Ecuador - Grace Carolina Guevara Rosero; Stephane Riou; Corinne Autant-Bernard (European Regional Science Association (ERSA), 2015)
The spatial agglomeration of economic activities play a crucial role on productivity but the composition of such an agglomeration is what really matters. There exists an ongoing debate between the predominance of the effects of agglomeration from specialization and diversity. This paper aims to estimate the impact of the type of externalities on the local sectoral productivity in Ecuador, a country of Latin American region for which literature gives little attention. When measuring agglomeration economies, one concern is the endogeneity issue. In this purpose, the instrumental variables method is implemented. We provide estimations using GMM model and we instrument the endogenous variable with a menace index, long lagged population density and spatial lags. Last, we investigate the specific role of urbanization. The intuition is that a critical level of urbanization is required to produce positive externalities as it guarantees the existence of a minimum level of transport and telecommunication infrastructures, of banking and financial services or other specific services. It is also a manner to capture the great heterogeneity of Ecuadorian cantons in terms of urbanization. Our empirical work is mainly based on the Economic Census of Ecuador 2010 which accounts for information declared in 2009. By aggregating the firm data, we build a two-digits industry database at the cantonal level. Precisely, our estimations are based on 86 industries and 221 cantons. From a first polled estimation on 7988 canton and industry pairs, our results suggest the existence of strong positive externalities from diversity impacting on the local productivity of industries and a lower impact of specialization. We also find economies of density, measured by the density of firms at the canton and industry levels that positively influence the local productivity of industries. Competition of firms has a significant negative effect. Moreover, we conduct regressions by distinguishing the manufacturing from the service industry. The magnitude of the externalities from diversity is positive and significant in manufacturing but much higher in the service industry. Interestingly, our regressions exhibit the non-monotonous effect of urbanization on the various externalities that impact on the local productivity. Precisely, the positive externalities arising from diversity are growing with the level of urbanization of cantons. Last, economies of density occur until a urbanization rate of 61%. Above this threshold, the economies of density cease to be positive suggesting that they are overcompensated by congestion effects. However, the effects of diversity and competition does remain highly positive, we therefore do not consider that the threshold of 68% represents excessive agglomeration.
Keywords: O54; L80; O18; L60; 330; agglomeration externalities; urbanization; Latin America; industry studies